The Natural History of Inflammatory Bowel Disease and Primary Sclerosing Cholangitis after Liver Transplantation – a Single-Centre Experience - Karli J Moncrief; Anamaria Savu; Mang M Ma; Vince G Bain; Winnie W Wong; Puneeta Tandon (Canadian Journal of Gastroenterology)
OBJECTIVE: To describe the natural history of primary sclerosing cholangitis (PSC) and inflammatory bowel disease (IBD) after liver transplant, the predictors of PSC and IBD recurrence, and the interaction of these disease processes.